Water Pump and Irrigation Monitoring System on ThingSpeak - Ahmad Kambali, Fatin Najiha; Yahaya, Jabbar Al-Fattah (Evolution in Electrical and Electronic Engineering, 2022)
This paper focuses on the use of modern irrigation method with the ability to monitor moisture of soil as irrigation process affect the crops yield production. For this paper, the work is aim to design an irrigation monitoring system on ThingSpeak integrating with the solar energy to allow the user in observing the data collected by Soil Moisture Sensor and DHT11 on ThingSpeak. The ESP8266 Wi-Fi module being used to allow the system connect with internet. This work employed gate driver connected with buck converter for controlling DC motor water pump through adjusting the PWM sequence using push button to control speed of water flow during irrigation process when the level of soil moisture below from set value. PWM charge controller connect with solar panel used for charge battery for supply power to the system and give power source to buck converter. The data presented on ThingSpeak is visualized in a line graph with collected values which is temperature (˚C) and humidity (%) from DHT11 and soil moisture (%) from Soil Moisture Sensor. It is concluded that the hardware design able to perform irrigation process using solar energy and the data collected by sensors can be monitored through Internet of Things (IoT) platform. In future, install the water level sensor for filling the water tank automatically will help to reduce user workloads. Further, possible attempt to allow the private Wi-Fi connect with the system should be study to build the system in bigger scale.